KONTRIBUSI PENDAPATAN USAHATANI KARET TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI KECAMATAN MUARA BELITI KABUPATEN MUSI RAWAS (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2021)
Farmer household as other household in general has done many economic activity to earn income. Household income comes from branch of business, farming and non farming. The aim of this research was to analyze income contribution of rubber farming toward farming household at Muara Beliti District of Musi Rawas Regency.Research methode was survey. From 838 farmer’s family, 41 sampling has choosen with Proportionate Stratified Random Samplingbased on land area. The result of this research shows that income contribution from rubber farming toward household income of rubber farmer at Muara BelitiDistrict Musi Rawas Regency as much as 55,38 percent, means high category. Meanwhile income contribution from non rubber farming as much as 4,44 percent(very low) and contribution from non farming as much as 40,18 percentalso in low category.Key Words: Contribution, Household, Rubber Farmer